2019
DOI: 10.22610/jebs.v10i6a.2661
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Turbulence on Product Innovation in Small to Medium Enterprises in Harare, Zimbabwe

Abstract: The purpose of the research was to examine the impact of environmental turbulence on product innovations in small to medium enterprises (SMEs). In the study environmental turbulence consisted of five dimensions namely, supplier turbulence, technological turbulence, market turbulence, regulatory turbulence and competitive intensity. A cross-sectional quantitative research design was adopted in the study. The study sample was drawn from a pool of 3,000 SMEs both unregistered and registered with the Ministry of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…To further understand the results, we delved deeper into the findings of two studies in the manufacturing context using environmental turbulence as the antecedent to innovation (Zimuto et al, 2018). Zimuto et al (2018) found that CI had the greatest association with innovationmarket innovation was higher in more competitive environments. In our service context, CI was negatively associated with innovation speed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To further understand the results, we delved deeper into the findings of two studies in the manufacturing context using environmental turbulence as the antecedent to innovation (Zimuto et al, 2018). Zimuto et al (2018) found that CI had the greatest association with innovationmarket innovation was higher in more competitive environments. In our service context, CI was negatively associated with innovation speed.…”
Section: Discussionmentioning
confidence: 99%
“…The more competitive the environment, the more likely that firms will try to find ways to increase their ability to read the environment, make rapid decisions on how to respond and accelerate the product development cycles as a basis for competitive advantage (Porter, 1979;Van Riel et al, 2004). CI has been found to have the greatest positive influence of the three environmental forces on innovation in manufacturing environments (Zimuto et al, 2018). The level of competitive activity forces B2B service firms to increase the speed of innovation (as well as service delivery efforts) to affect customer needs and stimulate new demand (Baddar-Alhussan et al, 2017): H4.…”
Section: Environmental Forces and Innovation Speedmentioning
confidence: 99%
See 3 more Smart Citations